2020
DOI: 10.1039/d0cc04109b
|View full text |Cite
|
Sign up to set email alerts
|

A 2D donor–acceptor covalent organic framework with charge transfer for supercapacitors

Abstract: A electron donor-acceptor covalent organic framework (TTF-COF1) was constructed by imine condensation of electron donor tetraformyl-tetrathiafulvalene (TTF-fo) and electron acceptor 2,6-diaminoanthraquinone (DAQ). TTF-COF1 involves in intramolecular charge transfer, offering a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…The other strategy is to introduce, usually via a bottom-up synthetic strategy, redox-active groups that could provide additional pseudocapacitor behaviour on the basis of electrochemical double-layer capacitor (EDLC) behaviour. For example, anthraquinone, 7 phosphine, 8 triazine, 9 and pyridine groups 10 have been successfully employed to construct pseudocapacitive COF materials. These redox-active groups could act quickly and effectively to absorb and release charge to provide effective and fast charging and discharging characteristics for supercapacitors.…”
mentioning
confidence: 99%
“…The other strategy is to introduce, usually via a bottom-up synthetic strategy, redox-active groups that could provide additional pseudocapacitor behaviour on the basis of electrochemical double-layer capacitor (EDLC) behaviour. For example, anthraquinone, 7 phosphine, 8 triazine, 9 and pyridine groups 10 have been successfully employed to construct pseudocapacitive COF materials. These redox-active groups could act quickly and effectively to absorb and release charge to provide effective and fast charging and discharging characteristics for supercapacitors.…”
mentioning
confidence: 99%
“…We observe that TAPA has NH stretching peaks 31 at 3407 and 3336 cm −1 , and TFPA has C═O stretching peaks 32 at 1692 cm −1 . Compared with the FTIR spectra of TFPA and TAPA, we can find that the stretching vibration peak of NH and C═O stretching vibration peak are disappeared in TPA‐COFs, and are replaced by a new C═N 36 (1618 cm −1 ) stretching vibration peak. Through the analysis of infrared spectroscopy, it can be proved that the raw materials are consumed and the target product is formed.…”
Section: Resultsmentioning
confidence: 94%
“…[67] Based on the influence of electron and hole mobility on HER catalytic activity, designing donor-acceptor (DÀ A) COFs has also received considerable attention from researchers. [68][69][70] For example, by the connection of electron-rich pyrene and electron-deficient thiazolo [5,4-d]thiazole, Wen group successfully synthesized a novel DÀ A COF (PyTz-COF) (Figure 9a). [71] The study showed PyTz-COF had an excellent ability for photoelectrochemical performance for HER.…”
Section: Hermentioning
confidence: 99%